Intraoperative Electrically Evoked Auditory Brainstem Response (eABR) examination in cochlear implant candidacy - Zizlavsky, Semiramis; Saleh, Rangga Rayendra; Priyono, Harim (Oto Rhino Laryngologica Indonesiana, 2024)
Background: Cochlear implantation is one of the most promising hearing habilitation methods for patients with profound sensorineural hearing loss (SNHL). One of the difficulties associated with the method is predicting the outcome of the surgery, especially in patients with cochlear nerve abnormalities. Purpose: To evaluate the intraoperative cochlear nerve response using Electrically Evoked Auditory Brainstem Response (eABR), and determine if cochlear implantation was required. Clinical question: How significant was intraoperative eABR in determining the outcome of cochlear implantation? Case report: This study considered two cases with profound bilateral SNHL that underwent intraoperative eABR. The first case involved 10-year-old girl who had used conventional hearing aids for eight years before surgery. She practiced lip reading for communication. The second case involved 4-year-old boy with delayed speech and a history of febrile seizure when he was two years old. He had used a conventional hearing aid for six months. Method: Evidence based literature was conducted through PubMed, Embase, and Wiley. Result: On the first case, eABR examination evoked no response in both ears and the parents decided not to carry on with the surgery. In the second case, eABR examination aroused a significant response in both ears, so the implantation was performed. Three months postoperative, the child was babbling and able to detect sound. Conclusion: eABR could give valuable input in identifying profound bilateral SNHL patients with cochlear nerve abnormality. The high cost of implant devices makes this examination beneficial for the patient’s family in deciding if implantation surgery is required.   Keywords: cochlear implant, cochlear nerve hypoplasia, eABR, hearing habilitation, profound sensorineural hearing loss